2021
DOI: 10.1016/j.micpath.2021.105008
|View full text |Cite
|
Sign up to set email alerts
|

Potential association of COVID-19 and ABO blood group: An Indian study

Abstract: Coronavirus disease 2019 (COVID-19) transmits from person to person mainly through respiratory droplets and coughing. Infection severity ranges from asymptomatic and mild infection to those with moderate and severe symptoms which may lead to multiple organ failure and mortality. Infection severity largely depends on individual's immune response, age and co-morbidities. Present study categorized COVID-19 infected patients based on their infection severity and linked COVID-19 severity with age, gender and ABO bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Dentali et al confirmed the link between ABO blood groups and thrombosis risk in general, in which individuals with non-O blood groups were more likely to experience thrombotic episodes of venous or arterial origin [ 6 ]. Another study found an association between ABO blood groups and viral infections such as rotavirus, norovirus (NoV), dengue virus, Norwalk virus, and hepatitis B virus [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dentali et al confirmed the link between ABO blood groups and thrombosis risk in general, in which individuals with non-O blood groups were more likely to experience thrombotic episodes of venous or arterial origin [ 6 ]. Another study found an association between ABO blood groups and viral infections such as rotavirus, norovirus (NoV), dengue virus, Norwalk virus, and hepatitis B virus [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study collects clinical profiles of 383 COVID-19 patients from India. Out of these patients, 251 were males and 132 were females [ 23 ]. Thrombotic parameters of 70 patients were recorded and correlated with the severity of infection and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…During the current pandemic, several studies have investigated the association of blood groups and COVID-19 [ 13–18 ]. Some studies suggested that patients with blood group A are more susceptible to severe infection, but there are other controversial results [ 19–24 ]. More studies are needed to confirm the association between blood grouping and COVID-19 susceptibility and severity.…”
mentioning
confidence: 99%